Comparison of clinical, radionuclide, and radiographic features of osteoarthritis of the hands. Issue 9 (September 1991) - Macfarlane, D G; Buckland-Wright, J C; Emery, P; Fogelman, I; Clark, B; Lynch, J
Abstract : Simultaneous clinical, scintigraphic, and macroradiographic assessments were carried out on 32 patients with hand osteoarthritis and the results at entry and one year reported. The presence and growth of osteophyte correlated with symptoms and a positive scan. The scan did not detect the radiographic features of juxta-articular radiolucencies, subchondral sclerosis, or cartilage thinning. Osteophytes, particularly when fast growing, produce pain, a 'hot' scan, and may predict disintegration of joint architecture.